Most commonly prescribed blood pressure lowering drug linked with increased risk of skin cancer. - Alam Rehmani, Soha; Alam Rehmani, Maha; Shoaib, Navaira (Journal of the Pakistan Medical Association, 2022)
To the Editor, Hydrochlorothiazide (HCTZ) is the most commonly prescribed antihypertensive drug that belongs to a diuretic class.1 It mainly works by increasing the removal of excess water and salts from the body into the urine and by this function it is most widely used alone or in combination with other medications to treat patients with uncontrolled blood pressure and edema that results from numerous medical conditions like heart, Liver and kidney diseases. It also helps treat other ailments like diabetes insipidus, renal tubular acidosis and reduce the risk of kidney stones in patients with high calcium levels in urine. Despite its various uses and benefits, HCTZ comes with a heavy price of undesirable side effects like fatigue, lethargy, gastrointestinal discomfort and is known to cause hyperuricemia and hypokalemia associated with increased blood glucose.2 Furthermore, HCTZ increases the skin sensitivity to sunlight. However, recent research has revealed a more worrisome side effect of HCTZ that needs to be highlighted. In 2017, a nationwide study conducted in Denmark involving more than 70,000 patients with Basal cell carcinoma and 8000 patients with squamous cell carcinoma found a considerably increased risk of developing Non melanoma skin cancer, particularly among the users of HCTZ.3 A recent study also substantiated that a total of 135 squamous cell carcinoma events per 100,000 person years were reported in new users of HCTZ.4 These alarming figures raise a question mark on the safety of HCTZ use. Moreover, HCTZ is now classified as a carcinogenic agent for humans by the International Agency for Research on Cancer and the U.S. Food and Drug Administration has also permitted changes to the HCTZ drug label to warn the health care workers and patients of the risk of non-melanoma skin cancer. 5, 6 Unfortunately in Pakistan, HCTZ is still heavily used as a diuretic and people are not much aware of this new fact. In view of these findings and the fact that HCTZ is among the most generally prescribed drugs in Pakistan, its potential indication of causing skin cancer would impose a serious public health concern so the responsibility lies on the cardiologists, nephrologists and other medical physicians to be aware of this possible hazardous outcome of HCTZ use and should be cautious while prescribing it to patients who are at risk of developing skin cancer or who have had a history of skin cancer.